The Implementation Of Project-Based Approach In Teaching English For High School Students - Rina Khafizah; Abdul Syahid; Zaitun Qamariah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The implementation of this project-based approach has many benefits and effective to be applied in the learning process so that students can be more active because they are required to complete a project so that can train cooperation in groups as a good team work is created. This research aims to observe the implementation of a project-based approach using drama projects with high school students and evaluate students' opinions regarding the use of drama projects in English learning assignments. Researcher used a qualitative case study design on grade 12 students divided into 3 classes at SMA Negeri 1 Kahayan Hulu Utara, Gunung Mas Regency, Central Kalimantan. Data was collected through observation checklist and interviews. The finding showed that English language teacher apply almost all the syntax of the project-based approach when teaching English language learning using drama projects as their assignment products and all high school students give positive responses to the use of this method in learning English which they consider increase students' creativity and effect their understanding when they feel interested in a subject because the approach used by the teacher concerned is interesting to them.